Development of Dance Learning Model at School - Aulya, Vinna; Yahya, Yahya (LANGGAM: International Journal of Social Science Education, Art and Culture, 2023)
This research was motivated because the learning activities of cultural arts at SMA Negeri 1 Koto Balingka were not carried out correctly. The teaching and learning process was carried out less than optimally, extracurricular activities did not go well. Therefore, this study aimed to 1) find out the model used in class IPA SMA N 1 Koto Balingka, 2) produce a dance learning model design in school, 3) obtain a dance learning model in school and 4) produce a dance learning model in school. This research was development research using a 4D development model (define, design, develop, and disseminate). The type of data generated was a product trial assessing the creative movement resulting from the educational dance learning model. The instrument used to collect data consisted of a validity questionnaire by validators/experts/experts. The data analysis techniques in this study were product validity analysis, product practicality analysis, product effectiveness analysis. The research results could be concluded that learning to design dance works using the Development of Educational Dance Learning Model based on Themes (RIDAMA) is very attractive to students. Dance learning activities were easy to understand. It could be seen from the value of the model's validity of 90.26 with very valid criteria. The value of the practicality of the model by the teacher was 93.4 with very practical criteria. In comparison, students' practicality of the model was 98 very practical criteria. The model's effectiveness consisted of an overall assessment of student activity with a score of 92 with very active criteria and student learning outcomes in the knowledge aspect with a score of 97 with a very good predicate. The study results concluded that the Theme-based Educational Dance Learning Model (MPTPbT) developed was valid, practical, and effective. This model can overcome the limitations of dance learning tools in schools.